Process of Self-Leadership: Establishing Yourself as Leader No Matter Your Role - George-Puskar, Annie; Beavers, Elizabeth; Bruns, Deborah; Lindner, Chloe (International Journal of Education Policy and Leadership, 2024)
As the field of early intervention/early childhood special education (EI/ECSE) focuses intently on building, supporting, and sustaining leaders across varying contexts and roles, this study introduced the concept of self-leadership to EI/ECSE self-identified leaders. The research explores differences in self-rated skills based on role, analyzes themes of goals for developing self-leadership skills, and analyzes the measurability of goals set by participants. Fifty-six participants completed the Abbreviated Self-Leadership Questionnaire (ASLQ) (Houghton, Dawley, & DiLiello, 2012), self-rated their own skills, and identified leadership goals. Results show that participants scored themselves highest on evaluating beliefs and assumptions about self-leadership. Self-identified goals resulted in three primary themes (administrative tasks, relationship building and coaching, and growth in learning). Directions for future research, policy, and recommendations for practice are discussed.